The Plot Thickens : Illustrated Victorian Serial Fiction from Dickens to Du Maurier - Leighton, Mary Elizabeth, 1971-; Surridge, Lisa A. (Lisa Anne), 1963- (Book collections on Project MUSE., 2019)
"In the early 1800s, books were largely unillustrated. By the 1830s and 1840s, however, innovations in wood- and steel-engraving techniques changed how Victorian readers consumed and conceptualized fiction. A new type of novel was born, often published in serial form, one that melded text and image as partners in meaning-making. These illustrated serial novels offered Victorians a reading experience that was both verbal and visual, based on complex effects of flash-forward and flashback as the placement of illustrations revealed or recalled significant story elements. Victorians' experience of what are now canonical novels thus differed markedly from that of modern readers, who are accustomed to reading single volumes with minimal illustration. Even if modern editions do reproduce illustrations, these do not appear as originally laid out. Modern readers therefore lose a crucial aspect of how Victorians understood plot--as a story delivered in both words and images, over time, and with illustrations playing a key role. In The Plot Thickens, Mary Elizabeth Leighton and Lisa Surridge uncover this overlooked narrative role of illustrations within Victorian serial fiction. They reveal the intricacy and richness of the form and push us to reconsider our notions of illustration, visual culture, narration, and reading practices in nineteenth-century Britain"--